2015
DOI: 10.1175/jas-d-14-0129.1
|View full text |Cite
|
Sign up to set email alerts
|

Wind and Temperature Oscillations Generated by Wave–Turbulence Interactions in the Stably Stratified Boundary Layer

Abstract: The authors investigate atmospheric internal gravity waves (IGWs): their generation and induction of global intermittent turbulence in the nocturnal stable atmospheric boundary layer based on the new concept of turbulence generation discussed in a prior paper by Sun et al. The IGWs are generated by air lifted by convergence forced by the colliding background flow and cold currents near the ground. The buoyancy-forced IGWs enhance wind speed at the wind speed wave crests such that the bulk shear instability gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
95
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 90 publications
(82 reference statements)
9
95
0
Order By: Relevance
“…In fact, wind speed perturbations induced by waves can enhance shear and thereby promote the onset of mechanically generated turbulence (orange whirls in Figure 4), which then also affects heat transport [186,200]. Actually, intermittent turbulence can be triggered in the SBL by a range of diverse sub-mesoscale (submeso) motions, of which orographically generated IGW are just one example [194,[201][202][203].…”
Section: The Role Of Gravity Wavesmentioning
confidence: 99%
“…In fact, wind speed perturbations induced by waves can enhance shear and thereby promote the onset of mechanically generated turbulence (orange whirls in Figure 4), which then also affects heat transport [186,200]. Actually, intermittent turbulence can be triggered in the SBL by a range of diverse sub-mesoscale (submeso) motions, of which orographically generated IGW are just one example [194,[201][202][203].…”
Section: The Role Of Gravity Wavesmentioning
confidence: 99%
“…The energy and momentum transported by GWs can be transferred to the mean flow, influencing local meteorology and global atmospheric circulations [10]. Moreover, instability and breaking of waves can produce clear air turbulence in the troposphere and can generate turbulence in the SBL that enhances the intermittent characteristics of turbulent transport of momentum, mass and energy [17]. The latter influences chemical mixing of aerosols, biogenic and anthropogenic gases.…”
Section: Introductionmentioning
confidence: 99%
“…While some progress has been made in the GW parameterisation within global models, description and parameterisation of the turbulence-wave interaction remain an open question, especially near the ground [17][18][19][20]. The discrimination between waves and turbulence is a focal point needed to make progress as these two motions have different properties with regards to heat, moisture and pollutant transport.…”
Section: Introductionmentioning
confidence: 99%
“…Although these phenomena are common in SBLs, it is not easy to find clear evidence of their existence given the fine horizontal and vertical resolutions required for such observations. Thus, only a few studies have reported in detail cases like the one here presented, as for example in Sun et al (2015a).…”
Section: Introductionmentioning
confidence: 83%